Elastic properties of 5d transition-metal carbides: An ab initio study - Mex, L.; Aguayo, A.; Murrieta, G. (Condensed Matter Physics, 2015)
We have systematically studied the mechanical stability of group V transition metal carbides TMC₂ (TM=Hf, Ta, W, Re, Os, Ir, Pt, and Au) in the pyrite and fluorite phase, by calculating their elastic constants within the density functional theory scheme. It was found that all but ReC₂ and OsC₂ are stable in pyrite phase. On the other hand, all metal carbides studied were unstable in the fluorite phase.